RETRACTED: Mental Health Problems Among Front-Line Healthcare Workers Caring for COVID-19 Patients in Vietnam: A Mixed Methods Study - Nguyen, Thu Kim; Tran, Ngoc Kim; Bui, Thuy Thanh; Tran, Len Thi; Tran, Nhi Tho; Do, Mai Tuyet; Nguyen, Tam Thanh; Tran, Huong Thi Thanh (Frontiers in Psychology, 2022)
Healthcare workers have directly provided care for COVID-19 patients, and have faced many additional sources leading to poor mental well-being. The study aimed to investigate the mental health problems and related factors among healthcare staff in Vietnam. A descriptive cross-sectional mixed methods study, combining quantitative and qualitative research methods, was performed among 400 healthcare workers working at the National Hospital for Tropical Diseases and Ninh Binh General Hospital from the first day of treatment for COVID-19 patients to May 01, 2020. The results showed that 8.0% of participants had stress, 17.5% of participants had anxiety, and 14.8% of participants had depression. Approximately 50% of participants reported that they had at least one of these symptoms. The findings illustrated that stress, anxiety, and depression were associated with the position in a hospital, health status during the COVID-19 pandemic, family members/relatives infected with COVID-19, physical and mental support from friends, family, and community, department, years of working, and the average work hours per day of healthcare workers exposed to COVID-19. In conclusion, during the COVID-19 pandemic in Vietnam, healthcare workers who worked in the hospital providing treatment and care for COVID-19 patients dealt with mental health problems such as stress, anxiety, and depression. It is necessary to promote mental health among healthcare workers, to contribute to the fight against the COVID-19 outbreak.